Developing and evaluating simulation-based pandemic preparedness training for prehospital emergency healthcare workers - Seval Çalışkan Pala; Selma Metintaş; Engin Özakın; Veli Görkem Pala (Journal of Emergency Management, 2026)
Objective: The primary objective of this study was to compare the effectiveness of computer-based simulation (CBS) and mannequin-based simulation (MBS) on post-training performance among prehospital emergency healthcare workers (PEHWs). Secondary objectives included evaluating within-group pre–post changes and assessing perceived training effectiveness. Methods: This quasi-experimental study was conducted in Türkiye between 2020 and 2021. After standardized online theoretical training, participants were allocated to CBS or MBS groups using propensity score matching based on age, gender, profession, and years of experience. Performance was assessed using a structured 20-item checklist before and immediately after training. Between-group differences in post-test scores were analyzed using analysis of covariance, adjusting for baseline values. Results: A total of 97 participants were included (CBS: 47; MBS: 50). No statistically significant differences were observed between the groups in terms of changes in mean performance scores. However, both groups demonstrated improvements in several domains. The CBS group showed greater gains in infection control and patient transfer, whereas the MBS group demonstrated improvements in patient assessment and communication domains. Conclusion: Both simulation modalities were associated with improvements in performance among PEHWs. No statistically significant difference was found between CBS and MBS in overall outcomes. These findings suggest that different simulation approaches may offer complementary contributions to training. Further studies with control groups and long-term follow-up are needed to evaluate sustained effects and optimize training strategies.